Digital workplace transformation - Sheiko, I. A.; Kurdenko, O. V. (ХНУРЕ, 2022)
The digital workplace is now more of a launching pad for business development than a strict requirement. People are now ready for a new type of workplace thanks to the use of technological resources and the development of Artificial Intelligence (AI). A new category of employee communication tools has emerged because of how people communicate daily.
Keywords: digital workplace